1993
DOI: 10.1002/hep.1840180606
|View full text |Cite
|
Sign up to set email alerts
|

Quantitation and typing of serum hepatitis C virus RNA in patients with chronic hepatitis C treated with interferon-β

Abstract: We quantified serum hepatitis C virus RNA titers and determined hepatitis C virus subtypes in chronic hepatitis C patients treated with interferon‐β to investigate relationships among serum ALT response, serum hepatitis C virus titer and hepatitis C virus subtype. Of 146 chronic hepatitis C patients who received interferon‐β therapy, 24 patients with sustained serum ALT normalization (complete responders) and 26 patients without serum ALT normalization (nonresponders) were randomly selected. Detection, typing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
38
1
1

Year Published

1994
1994
2004
2004

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(42 citation statements)
references
References 26 publications
2
38
1
1
Order By: Relevance
“…Despite the risk of proteinuria, we elected to use IFN-, as the shorter duration of treatment was less likely to pre- cipitate renal rejection. IFN therapy is especially effective in patients with a low viral load and with HCV sero-group 2 (15,16,18), as in the present case. Recently, combination therapy with IFN-and ribavirin has been used for patients with a high viral load or with relapse, and higher rates of sustained-response have been achieved (19,20).…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Despite the risk of proteinuria, we elected to use IFN-, as the shorter duration of treatment was less likely to pre- cipitate renal rejection. IFN therapy is especially effective in patients with a low viral load and with HCV sero-group 2 (15,16,18), as in the present case. Recently, combination therapy with IFN-and ribavirin has been used for patients with a high viral load or with relapse, and higher rates of sustained-response have been achieved (19,20).…”
Section: Discussionsupporting
confidence: 57%
“…IFN-is typically administrated as daily intravenous infusions for 6 to 8 weeks. While the duration of IFN-treatment is shorter than that of IFN-, intravenous IFN-therapy appears to be as effective as IFNtherapy (15,16), but does have a higher incidence of inducing proteinuria. The increase in proteinuria is not due to renal injury per se, but rather may be secondary to neutralization of the anionic charge of the glomerular basement membrane (17).…”
Section: Discussionmentioning
confidence: 99%
“…Viraemia quantification may be assessed by a new assay that uses a branched DNA (bDNA) signal amplification [9]. It has been suggested that quantitative study of HCV RNA may be useful since patients with low HCV viraemia are likely to respond to interferon therapy [10]. Development of a chronic liver disease occurs in at least 50% of infected patients [II].…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19] Although IFN-␤ binds to the same cell surface receptor as IFN-␣, it has been suggested that a second, receptor-associated protein is involved in generating specific downstream signals in response to IFN-␤. 20 Indeed, recent data highlight the fact that IFN-␣ and IFN-␤ trigger distinct biological responses in vitro.…”
mentioning
confidence: 99%